A rare case of vernakalant-induced 1:1 atrial flutter during chemical cardioversion of atrial fibrillation requiring emergency direct current cardioversion. (2nd June 2021) - Stoneman, Paul; Adams, Joseph; Colbert, Fiona; Sheahan, Richard
Abstract : Vernakalant is an atrial-selective, multi-channel anti-arrhythmic that offers a safe alternative to traditional approaches to chemical cardioversion of recent-onset, non-valvular atrial fibrillation. This case report describes a very rare occurrence of unstable accelerated 1:1 atrial flutter during an attempted cardioversion of non-valvular atrial fibrillation using vernakalant hydrochloride that required emergent direct current cardioversion. This case report highlights the need for clinicians to remain vigilant and be prepared to treat rare consequences of vernakalant administration.